Studi Literatur: Hubungan Pengetahuan K3 Dengan Kejadian Kecelakaan Kerja - Fatma Sri Ramadhan Lubis; Kholid Abdullah Yasin; Fuad Baazir; Sri Hajijah Purba (Lembaga Pengembangan Kinerja Dosen, 2024)
Knowledge of Occupational Safety and Health (OSH) plays an important role in reducing the incidence of occupational accidents. This article aims to conduct a literature review on the relationship between the level of knowledge about occupational safety and health (OSH) and the incidence of occupational accidents, referring to the findings. In writing using the literature review method, this approach is a structured, detailed and iterative process that aims to identify, present and integrate research findings and views from researchers and practitioners. The results of research conducted using the literature method found that there is a relationship between knowledge and the incidence of work accidents. So it can be concluded that knowledge has a significant relationship with the incidence of work accidents.